Design of Connectivity Preserving Flocking Using Control Lyapunov Function - Bayu Erfianto; Riyanto T. Bambang; Hilwadi Hindersah; Intan Muchtadi-Alamsyah (Journal of Robotics)
This paper investigates cooperative flocking control design with connectivity preserving mechanism. During flocking, interagent distance is measured to determine communication topology of the flocks. Then, cooperative flocking motion is built based on cooperative artificial potential field with connectivity preserving mechanism to achieve the common flocking objective. The flocking control input is then obtained by deriving cooperative artificial potential field using control Lyapunov function. As a result, we prove that our flocking protocol establishes group stabilization and the communication topology of multiagent flocking is always connected.